Study Of the Effect of Operating Frequency on The Needle Antenna Used in The Treatment Hepatic Tumors by Microwave - S.B.Almabrok; M.M.Abulaweenat; Y.A.Abdulkarim (Journal of Pure & Applied Sciences, 2022)
Microwave ablation (MWA) is a type of heat therapy, and it is a process that uses heat from microwave energy to destroy cancer cells, a coaxial antenna (needle) is inserted into biological tissues, and the radiation emitted from the antenna is absorbed by the tissues and causes the cancer cells to heat up. This paper aimed to study the interaction between electromagnetic waves with tissues for treating liver cancer, and this was done by performing a two-dimensional digital simulation using the finite element method, and Maxwell's equations and bio-temperature equation are used to estimate the electric field and temperature distribution in liver tissues, and the heat is generated by the antenna to destroy the cancer cells. In addition, the effect of operating frequency on the performance of the needle antenna was studied by analyzing the electrical and thermal effects to find out the specific absorption rate (SAR), the temperature distribution in the liver tissue, and the damaged portion of the cancer cells. The numerical results showed that the absorbed power density, the surface distribution of the temperature and the specific absorption rate, as well as the damaged part of the tumor are affected by the operating frequency, and the results showed that the relationship between the heating time of the tumor with the diameter of the destroyer that was destroyed was 100% the best time used at t = 10min, As it was found that this time was the best time for the size of the tumor under study after its use, and the largest diameter was destroyed when increasing the frequency d = 20mm.